Application of sliding mode control with extended high gain observer to stabilize the underactuated quadrotor system - Mohd Nor, Elya; Mohd Noor, Samsul Bahari; Abdul Rahman, Ribhan Zafira; Md Ali, Syaril Azrad (Universiti Putra Malaysia Press, 2017)
This work proposes an output feedback controller for stabilization of the quadrotor underactuated system in the presence of time varying disturbances and model uncertainties. The proposed control is an improvement to the sliding mode control (SMC). An extended high-gain observer (EHGO) when combined with sliding mode control (SMC) able to give feasible performance beyond the performance of the standard sliding mode. It is able to bring the state trajectories of the closed-loop system close to the target system with a smaller ultimate bound of error and smaller control magnitude. The proposed method is illustrated by simulation.